Valuasi Saham dan Pengambilan Keputusan Investasi: Perbandingan Metode Absolute dan Metode Relative - Tasya Natalia Pengestika; Ari Christianti (Jurnal Bisnis dan Manajemen, 2021)
One of the benefits of stock valuation is that it helps investors in making investment decisions. This study aims to compare the intrinsic value of shares using absolute and relative methods. The absolute method used in this study consists of the Dividend Discounted Model (DDM), Discounted Cash Flow (DCF), and Free Cash Flow to Equity (FCFE) while, the relative method consists of Price Earning Ratio (PER), Price to Book Value ( PBV), and Price to Sales (P/S). This study uses four samples of cement sub-sector companies listed on the Indonesia Stock Exchange in 2015-2019. The results based on the measurement of the accuracy of the stock valuation method with Root Mean Squared Error (RMSE) indicate that the DDM approach is the most accurate compared to others. In addition, the results of this study recommend investors sell shares coded INTP because the stock price is included in the overvalued and buy shares coded SMBR, SMGR, and WTON because the stock price is classified as undervalued. However, stock valuation does not fully determine investment success, so investors still have to consider the assumptions of each stock valuation model.